Inleiding tot de Latijnse Syntaxis Structuur van zin en tekst. Grammatica - Kroon, Caroline (Amsterdam University Press, 2007)
Latin Syntax is a concise overview of the Latin syntax, based on modern academic insights. This book offers clear understanding of the most important characteristics of Latin grammatical sentence structure. The emphasis lies on acquiring knowledge of the language system as a whole, than on learning loose facts. In a separate chapter textual grammar is fully analysed, therefore linking it to the increasing attention that is given to acquiring translation strategies in high school education. This challenging course was developed in the daily routine of Latin university education. Latin teachers and students have been using this method for years, and it is now accessible through this book. Latin Syntax is accompanied by an exercise book provided by Mieke Koenen (VrijeUniversity Amsterdam). The exercise material is based on authentic Latin texts and sentences. Both books are also suitable for anybody with a general interest in Latin who wants to expand or keep their knowledge up-to-date.